MARTINS, Patrícia; ANGHEL, Golgona; GUERREIRO, Fernando (Org.). Central de Poesia: a recepção de Fernando Pessoa nos anos 40. Lisboa: CLEPUL/ FLUL, 2011 - Bender, Mires Batista (Navegações, 2012)
xxxxx